The assessment of the association between systemic diseases and dental findings - (:unkn) unknown (My University, 2023)
Objective: In dentistry, systemic diseases are extremely important in terms of taking the required precautions for overall health and preventing complications before they emerge. Many clinicians are aware of the oral symptoms of systemic diseases; nevertheless, the major source of the problem must be addressed in order to limit the rate of misdiagnosis due to systemic origins and establish an appropriate treatment strategy. The purpose of this study is to investigate whether there is a relationship between systemic diseases and dental health. Methods: The study included 200 individuals, 100 women and 100 men, all between the ages of 25 and 75, who had at least one systemic disease. The patients’ medical records and panoramic radiography were examined. In the panoramic radiographs of the patients, the existence of existing teeth, caries, restorations, prostheses, and endodontic conditions were documented, taking into consideration the presence of systemic disorders, gender, and age of the patients. Results: Caries rates were significantly higher in the 25-40 age group (43.3%) than in the 41-60 age group (20.7%) (p<0.05). There was no statistically significant difference between the incidence of caries, endodontic treatment and prosthesis according to the presence of diabetes mellitus (p>0.05). The prevalence of prosthesis was statistically significantly greater in patients with cardiovascular disease (64.3%) than in patients without cardiovascular disease (47.7%) (p<0.05). Conclusion: According to the findings of our study, which confirm the link between oral and overall health, challenges with general health lead to several other adverse consequences, including worsening of dental health and related complications.
Keywords: Diagnosis; Oral; Dental Health Survey; Cardiovascular Diseases; Diabetes Mellitus